The Public Library of the Future: The Community Information Services Model for Ghana - Mfum, Christopher (Ghana Library Journal, 2012)
The paper discusses the potential of the public library in Ghana taking on the Community Information Services (CIS) model which has been tried and tested successfully in other national jurisdictions. By definition. Public Libraries are gateways to knowledge and information for the local community. However, with the failure of current strategies tomake public library services in Ghana attract Significant patronage and create special impact on users. the researcher believes that the CIS model could be exploited as it has the potential to contribute towards local economic development by satisfying the information needs of citizens. local enterprises. upcoming entrepreneurs and local community organizations. This outlook of the public library as a Community Information Service ensures enhanced linkages. community ownership and integration between the public library and the community it is established to serve.